An NHS Trust and others v Y and another [2018] UKSC 46: Reducing the Role of the Courts in Treatment Withdrawal. (15th January 2019) - Wicks, Elizabeth
Abstract: In An NHS Trust and others v Y and another, the Supreme Court was asked to address the question of whether a court order must always be obtained before clinically assisted nutrition and hydration (CANH), which is keeping alive a person with a prolonged disorder of consciousness (PDOC). This case note explores the Court's decision to dispense with the need for such a court order and analyses that important change in approach from the perspective of the right to life protected in Article 2 European Convention on Human Rights (ECHR) as well as in the broader context of end of life decision-making.